2020
DOI: 10.1016/j.bbmt.2020.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Hepatic Veno-Occlusive Disease/Sinusoidal Obstruction Syndrome

Abstract: Veno-occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) is a potentially life-threatening complication of hematopoietic cell transplantation. Early diagnosis and, subsequently, earlier intervention have been shown to be beneficial to clinical outcomes. Diagnostic criteria from the European Society for Blood and Marrow Transplantation include recommendations on the use of imaging for diagnosis. This review discusses evidence on the use of imaging in the management of VOD/SOS and how imaging biomarkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Therefore, structural liver stiffness measurements including baseline measurements are now increasingly advocated in patients at risk of developing sinusoidal obstruction syndrome in order to stratify those who could benefit from early defibrotide treatment [ 14 ] . Most recently, Chan et al [ 23 ] have summarized the available literature on US elastography in sinusoidal obstruction syndrome.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Therefore, structural liver stiffness measurements including baseline measurements are now increasingly advocated in patients at risk of developing sinusoidal obstruction syndrome in order to stratify those who could benefit from early defibrotide treatment [ 14 ] . Most recently, Chan et al [ 23 ] have summarized the available literature on US elastography in sinusoidal obstruction syndrome.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Medical imaging examination is of great value for the diagnosis and treatment of HVOD. The common Doppler US manifestations of patients with HVOD are: (I) a diffuse increase in liver volume, dense enhancement of parenchymal echo, uneven distribution, and a "map-like" change; (II) the diameter of hepatic veins becomes thinner and blood flow velocity slows down; (III) the portal vein diameter widens, the flow velocity slows down and even the reflux Ascites, gallbladder wall edema, umbilical vein opening and other manifestations of portal hypertension (22)(23)(24)(25)(26). Trenker et al (27) found that contrast-enhanced US allows assessment of the vascular supply of organs by using a purely intravascular contrast medium and contend that ultrasound contrast is helpful for the diagnosis of HVOD.…”
Section: Calculated Thatmentioning
confidence: 99%
“…The most valuable imaging feature that distinguishes BCS from HVOD is whether the main hepatic veins and IVC lumens are unobstructed. Color Doppler US combined with pulsed Doppler US can be used as a reliable method for rapid and noninvasive diagnosis of HVOD (24,25).…”
Section: Calculated Thatmentioning
confidence: 99%
“…Although definitive benefits remain inconclusive, magnetic resonance imaging and gray-scale and color Doppler ultrasonography have been used for accurate assessment of liver size, the presence of ascites [13], thickening of the gallbladder wall [37] and absence/presence of vascular flow and flow direction [38]. With the new pediatric EBMT guidelines, baseline ultrasound imaging might become mandatory for children [39].…”
Section: Hepatic Relatedmentioning
confidence: 99%
“…With the new pediatric EBMT guidelines, baseline ultrasound imaging might become mandatory for children [39]. Elastography is a non-invasive imaging modality that maps the elastic properties and stiffness of soft tissue and may be a reasonable strategy to evaluate the presence of portal hypertension based on a liver stiffness value >21 kPa [38,40,41]. Serialultrasoundelastographymay also hold the potential for helping clinicians predict early onset of SOS/VOD.…”
Section: Hepatic Relatedmentioning
confidence: 99%